2021
DOI: 10.1038/s41598-020-78208-2
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and caspases serum protein levels and survivin variants mRNA expression in sepsis

Abstract: Sepsis is a dysregulated host response to infection related to devastating outcomes. Recently, interest has been shifted towards apoptotic and antiapoptotic pathobiology. Apoptosis is executed through the activation of caspases regulated by a number of antiapoptotic proteins, such as survivin. The survivin and caspases’ responses to sepsis have not yet been elucidated. This is a multicenter prospective observational study concerning patients with sepsis (n = 107) compared to patients with traumatic systemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…However, what is shown for the first time is that the expression of three anti-apoptotic survivin splice variants was upregulated in peripheral blood leukocytes, which, along with elevated serum survivin protein, was associated with repressed TAC and mortality in sepsis. This is in agreement with the findings of a recent study, showing that seemingly antagonistic pathways of both pro- and anti-apoptotic genes are simultaneously upregulated early in the course of sepsis [ 29 ]. New therapeutic agents, increasing ATP production and the activities of mitochondrial complexes I and III in LPS-stimulated cardiomyocytes, have recently been found to reduce the LPS-induced levels of reactive oxygen species by suppressing cleaved caspase 3 activity [ 71 ] or by increasing the activities of antioxidant enzymes, glutathione peroxidase, superoxide dismutase, and GSH [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, what is shown for the first time is that the expression of three anti-apoptotic survivin splice variants was upregulated in peripheral blood leukocytes, which, along with elevated serum survivin protein, was associated with repressed TAC and mortality in sepsis. This is in agreement with the findings of a recent study, showing that seemingly antagonistic pathways of both pro- and anti-apoptotic genes are simultaneously upregulated early in the course of sepsis [ 29 ]. New therapeutic agents, increasing ATP production and the activities of mitochondrial complexes I and III in LPS-stimulated cardiomyocytes, have recently been found to reduce the LPS-induced levels of reactive oxygen species by suppressing cleaved caspase 3 activity [ 71 ] or by increasing the activities of antioxidant enzymes, glutathione peroxidase, superoxide dismutase, and GSH [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…The intracellular cumulative transcriptional mRNA expression of survivin in white blood cells was assessed through real-time quantitative polymerase chain reaction (qPCR), which was performed on the complementary DNA (cDNA), using reverse primers and hybridization probes, specific for the genes of interest for each splice variant of survivin (RNA extraction and reverse transcription for cDNA synthesis). New forward and reverse primers for each variant were designed to prevent non-specific amplifications [ 29 ]. Total mRNA was isolated from blood samples and K652 human cell line, using the Trizol reagent (Monarch Total RNA Miniprep Kit, NEB #T2010, New England Biolabs, Herts SG4 0TY, UK) and reverse transcription was performed using an iScript cDNA synthesis kit (BioRad, 1708891, Hercules, CA 94547, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has correlated increased pro-apoptotic-caspase-3/9 and anti-apoptotic survivin expression with higher instances of mortality in septic patients. 52 Another study demonstrated an increase in oxidative stress along with the upregulation of these proteins in septic patients compared to both non-septic trauma patients and healthy individuals. It was also found that these factors are related to anti-apoptotic, inflammatory, and innate immunity alterations in sepsis.…”
mentioning
confidence: 99%
“…Inhibitor of apoptosis protein (IAP) is a natural caspase inhibitor, and survivin is a member of the IAP family, which directly or indirectly suppresses the activity of caspase-3 and caspase-7. Survivin can also interfere with the activity of caspase-9 and block mitochondria-mediated apoptosis (17,18). Previous studies indicated that survivin was widely expressed in gastric, liver, lung, breast, and prostate cancers, but it was not expressed or showed low expression in adjacent tissues, making survivin a potential tumor marker (19).…”
Section: Original Articlementioning
confidence: 99%